Ihtibak in Al-Biqa'i’s Exegesis of Surah Yasin: ‎ A Theoretical and Applied Study ‎ - Abdul Wahab Almunawar; syafruddin syafruddin; Toni Markos; Sesra Ayu Ningsih (Universitas Islam Negeri Imam Bonjol Padang, 2025)
The concept of al-Ihtibak according to al-Biqa’i indicates the presence of intertwined structures in sentences, where one structure refers to a statement without the need for repetition in the other. Al-Biqa’i adopts a different explanatory approach, considering verses containing